EXPERIMENTAL STUDY ON ANTI-FREEZING ADHESIVE ROLLER WITH PTFE - WANG ChunHua; QU Hui; WANG ZhongXian; XU HanWen (Jixie qiangdu)
In order to study the turnabout roller coal slime freezing adhesion problem in the process of open-pit mine during winter,experimental apparatus was designed by ourselves,simulated the production site,studied the change of freezing adhesive characteristics of different material in different temperature and different freezing time condition. The results show that different materials and dry basis moisture content 40% of the coal slime have different freezing adhesive strength,among them PTFE material in normal and tangential freezing adhesive strength is lower than other materials,2. 5hours at- 25℃,normal freezing adhesive coefficient is 0. 037 MPa,tangential freezing adhesive coefficient is 0. 076 MPa,it is about 1 /3 of UHMW-PE material ’s normal freezing adhesive coefficient,and about 1 /6 of it’s tangential freezing adhesive coefficient; it is about 1 /44 of Q235 material’s normal freezing adhesive coefficient,and about 1 /19 of it’s tangential freezing adhesive coefficient,It illustrates PTFE has good antifreezing adhesive ability. Tests also show that temperature of freezing adhesive strength has a certain influence,but is not a linear relation; After 3 hours freezing adhesive strength change is small; Material of tangential freezing adhesive coefficient is usually larger than normal freezing adhesive coefficient; Surface freezing adhesive strength is independent of how much coal sample.